2018
DOI: 10.17245/jdapm.2018.18.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood flow at the mandibular angle and Horner syndrome in a rat model of superior cervical ganglion block

Abstract: BackgroundA stellate ganglion block (SGB) causes increased blood flow in the maxillofacial region, exhibiting the potential for regenerative effects in damaged tissue. The focus of this study was to understand the efficacy of SGB for regenerative effects against nerve damage. A rat model of the superior cervical ganglion block (SCGB) was created instead of SGB, and facial blood flow, as well as sympathetic nervous system function, were measured.MethodsA vertical incision was made on the left side of the neck o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
9
0
5
Order By: Relevance
“…SGB was originally used to relieve cancer pain. With the continuous deepening of research, it has been found that SGB can not only act on the head and neck, upper chest, and upper limbs, but also the immune system, endocrine system, cardiovascular system, and so on [ 10 ]. A large number of studies have shown that SGB can block the preganglionic and postganglionic fibers of the sympathetic nerve, inhibit the excitatory conduction of it, and inhibit the vascular and glandular activities in its innervated areas; increase the blood flow of the innervated areas such as the head, face, and vertebrobasilar artery, improve tissue oxygen supply, and reduce the damage of oxygen-free radicals; block the excessive activation of the hypothalamus–pituitary–adrenal axis and inhibit the stress response [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…SGB was originally used to relieve cancer pain. With the continuous deepening of research, it has been found that SGB can not only act on the head and neck, upper chest, and upper limbs, but also the immune system, endocrine system, cardiovascular system, and so on [ 10 ]. A large number of studies have shown that SGB can block the preganglionic and postganglionic fibers of the sympathetic nerve, inhibit the excitatory conduction of it, and inhibit the vascular and glandular activities in its innervated areas; increase the blood flow of the innervated areas such as the head, face, and vertebrobasilar artery, improve tissue oxygen supply, and reduce the damage of oxygen-free radicals; block the excessive activation of the hypothalamus–pituitary–adrenal axis and inhibit the stress response [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…On day 10 after initiation of SGB and 3 months postoperatively, all CPT values were signifi cantly lower in group L than in group M. CPT values at 2,000, 250, and 5 Hz, on day 10 after initiation of SGB were 72 (58-84), 44 , and 47 in group M, 44 (41.5-50), 28 (23.5-35) and 27 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) in group L, 3 months postoperatively were 48 (42-52), 28 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and 27 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) in group M and 33.5 (30)(31)(32)(33)(34)…”
Section: Qst Resultsmentioning
confidence: 88%
“…In a rabbit model, SGB increased blood flow in the craniocervical region [27] and changed the tissue oxygen tension of the mental nerve [28]. In a rat model, SGB increased blood flow at the mandibular angle [29], promoted neurophysiological recovery and regeneration of damaged infraorbital nerves at an early stage [11], and was effective in a facial palsy model [30]. In another study, sympathetic ganglion block in dogs exhibited an increase in oral mucosal blood flow and nasal skin temperature, and IAN repair using polyglycolic acid-collagen tubes resulted in a significantly higher degree of nerve regeneration due to the progression of myelin sheath maturation and thickening [31].…”
Section: Discussionmentioning
confidence: 99%
“…The typical pathological feature of EGPA is necrotizing small vessel vasculitis accompanied by eosinophilic infiltrates and perivascular and extravascular granulomas, leading to ischemia of the involved organs [ 4 ]. SGB averts sympathetic innervation, resulting in peripheral vasodilatation and increased perfusion [ 11 ]; consequently, it is widely used to treat a variety of ischemic disorders of the head, chest, face, and upper extremities. Furthermore, SGB may directly suppress inflammation and edema of the vascular wall [ 8 ].…”
Section: Discussionmentioning
confidence: 99%